PERFORMANCE EVALUATION OF DIALLYL DISULFIDE (DADS) AS A SOIL UREASE INHIBITOR - MANOGARAN, M.DEVENDRAN (2021)
Urease inhibitors have been introduced as a mitigation approach to reduce nitrogenous loss experienced by urea fertilizer when applied to soil. Diallyl disulfide (DADS) is an organosulfur compound similar to allicin and diallyl trisulfide (DATS) which have been recognized for their urease inhibitory traits attributed to the disulfide bond present in their structure. DADS also constitutes of the disulfide bond hence, it is expected that DADS inhibits urease activity as well. This research aims to optimize DADS’s concentration and duration of inhibition, determine stability of DADS in an enzymesubstrate- inhibitor interaction under different soil conditions and determine the kinetic parameters of soil urease affected by the inhibitory property of DADS as well as categorize the mode and type of inhibition.